Bittransfer: Mitigating Reactive Jamming in Electronic Warfare Scenarios - Savio Sciancalepore (16864152) (2019)
Electronic Warfare (EW) scenarios contemplate powerful and stealthy jamming attacks, able to disrupt any competing wireless communication in the target area. Reactive jamming techniques are especially suitable to this aim. Indeed, by first eavesdropping on the whole radio spectrum used for communications, and then timely injecting random noise as soon as a transmission is detected, reactive jamming represents both an effective and hard-to-detect attack tool. In such a challenging EW scenario, all the solutions currently available in the literature to mitigate reactive jamming require either the deployment of specialized hardware, or the modifications of physical layer protocols-the former solution being expensive, and the latter one usually not viable when considering commercially available wireless devices. In this paper we propose BitTransfer, an anti-jamming protocol enabling wireless communications between neighboring devices even under the above-described stringent requirements and powerful attacker model. BitTransfer embeds information bits in radio activity operations, a 0 being represented by the absence of any radio activity, and a 1 by the reception of a (corrupted) packet at the receiver. To demonstrate its applicability to a wide class of commercial wireless devices, BitTransfer has been implemented using a real constrained hardware platform (the Openmote-b), released as freely available and open-source, and tested using the IEEE 802.15.4 communication technology, adopted within the Bluetooth and Zigbee 3.0 protocol stacks. When under attack by a reactive jammer, BitTransfer can transfer a message of 127 Bit in 11.17 seconds, while competing approaches simply fail. Other than being completely tunable, BitTransfer can also enjoy further improvements by simply increasing the transmission rate of the devices. Finally, its detailed design, open-source availability, robustness, and superior performance when compared against competing solutions, make it a solution of choice in challenging EW scenarios, also paving the way to further research along the highlighted directions. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2019.2949716